The meaning of sex genes [and] gender - Barbara J. Meyer, lecturer; David C. Page, lecturer (Howard Hughes Medical Institute, 2003)
Why does sex exist, and what is its purpose and function? What decides whether an individual will be male of female? How are chromosomes, genes, and molecules involved in determining sex? In four lectures, two leading scientists in the field of sex-determination research answer these questions.